Kearifan lokal sasi ikan lompa masyarakat Desa Haruku dalam menjaga kelestarian ekosistem laut: Studi literatur - Anisa, Zeranita Ageng Nur; Surtikanti, Hertien Koosbandiah (Social, Ecology, Economy for Sustainable Development Goals Journal, 2024)
The local wisdom of the Maluku traditional community, especially in the practice of sasi, shows a strong understanding of the importance of nature conservation and sustainable use of natural resources. In the management of natural resources, sasi law, which is recognized both written and unwritten, is an important basis. Sasi, which is considered sacred and combines religious and traditional values, plays an important role in preserving the environment. This practice is becoming more and more crucial in the face of growing environmental harm from irresponsible behavior on the part of some people. Using secondary data found, evaluated, and integrated from previous research on the local wisdom of Sasi Ikan Lompa, this research uses literature, documents, books, and various scientific journals. The research results show that lompa fish sasi in Haruku Village, which is supported by established regulations, shows the awareness of indigenous peoples about environmental conservation. The lompa fish sasi is closed when the fish reaches the age of seven months, when the fish is in the nener phase. Coastal communities also harvest lompa fish as bait and food. Lompa fish is used as a main side dish and bait, and the people of Haruku Village also sell it to earn money. Lompa fish that is not sold can be consumed immediately or preserved for use in the next few months. The indigenous people of Haruku Village really hope to maintain and preserve local wisdom about sasi ikan lompa. This is important to maintain marine ecosystems, maintain the abundance of lompa fish, and help the community.